1984
DOI: 10.1007/bf00047659
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the microcirculation in tumors

Abstract: This review describes some aspects of tumor vessels and the influence of vasoactive agents on tumor blood flow, particularly the characteristic microcirculation of tumors with regard to its selective increase in blood flow. Elevation of blood pressure by infusion of angiotensin II produced a severalfold increase in tumor blood flow. The increase was selective and specific to the tumor vessels as long as the mean arterial blood pressure was kept under 150 mm Hg. Pressure elevation by angiotensin II also selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…A weak response was obtained to angiotensin II and adrenalin in neoplastic tissue only after administration of a dose 10-100 fold greater than that which evoked a response in the control neovasculature. Suzuki et al (1984) observed that newly growing tumour vessels did not react to topically administered angiotensin II. The vessels supplying tumours have been reported to be relatively unreactive to locally applied drugs which act on smooth muscle (Hirst et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A weak response was obtained to angiotensin II and adrenalin in neoplastic tissue only after administration of a dose 10-100 fold greater than that which evoked a response in the control neovasculature. Suzuki et al (1984) observed that newly growing tumour vessels did not react to topically administered angiotensin II. The vessels supplying tumours have been reported to be relatively unreactive to locally applied drugs which act on smooth muscle (Hirst et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…A similar progressive loss in the capacity to react to vasoactive agents by blood vessels in experimental mammary tumours as the tumours enlarged was reported by Wickersham et al (1977). A possible explanation for the progressive loss of reactivity in tumour, but not control, implants could be that, unlike the vessels of inflammatory granulation tissue, tumour vessels are characterised by a steady progression to necrosis without any intervening stable maturation phase (Suzuki et al, 1984). Another contributing factor could be that during neoplastic growth some of the preexisting host vessels incorporated in the tumour mass disintegrate, are obstructed or are compressed (Vaupel et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most other vasodilators also did not increase blood flow to experimental tumours, including phenoxybenzamine, isoprenaline, papaverine and hydralazine (Jirtle et al, 1978;Debreczeni et al, 1980;Mattsson et al, 1982;Chan et al, 1984). Tumour perfusion depends on the relative vascular resistance of the tumour and host circulations and on systemic blood pressure (Chan et al, 1984;Suzuki et al, 1984). Only doses of verapamil and flunarizine which reduced tumour vascular resistance without reducing blood pressure increased tumour blood flow (Kaelin et al, 1982; and the associated change in tumour FDCO would have been detectable by 86Rb.…”
Section: Discussionmentioning
confidence: 99%
“…histopathology ; induced hypertension chemotherapy ; angiotensin II ; gastric carcinoma Suzuki et al (1981Suzuki et al ( , 1984 in an effort to enhance the effect of cancer chemotherapy. It exploits the peculiar microcirculation of cancer tissue, where, due to lack of autoregulation which is present in ordinary tissues, blood flow is susceptible to fluctuation : The flow strongly increases when the systemic blood pressure is temporarily elevated by angiotensin II.…”
mentioning
confidence: 99%